A Novel Mixed-Mode Current-Controlled Current-Conveyor-Based Filter - Muhammad Taher Abuelma'atti (Active and Passive Electronic Components)
A new mixed-mode biquad circuit is presented. The circuit uses four dual-output second-generation currentcontrolled current-conveyors (DOCCCIIs) and two grounded capacitors and can realize lowpass, highpass, bandpass and notch responses from the same topology. The circuit can be driven by voltage or current and its output can be voltage or current. The parameters ωo and ωo /Qo enjoy independent electronic tunability. Simulation results are included.